Numerical simulation using the bubble size distribution model of cryogenic cavitation around an axial helical inducer. Issue 6 (March 2019) - Ito, Y; Zheng, X; Nagasaki, T
Abstract: A mathematical model using a bubble size distribution was developed by the author for a cryogenic high-speed cavitating flow in turbomachinery. In this model, bubble growth/decay is solved for each class of the bubble mass (as an accurate expression of bubble size) when bubbles with various masses mix in the same spatially discretized calculation region. The bubble growth/decay calculations employ a combination of two rigorous methods: a Rayleigh–Plesset equation for the bubbles' oscillation, and a heat conduction equation in a thermal boundary layer around a bubble to evaluate the mass rate of evaporation or condensation. This mathematical model was coded using the OpenFOAM C++ toolbox, and a numerical simulation was conducted for a 3D rotational inducer in a cryogenic fluid, the results of which showed that bubbles of a certain specified size were distributed at certain regions on the inducer. This study demonstrated that the mathematical model of cavitation exhibits potential to contribute to fidelity in simulation for turbomachinery considering a fluid with strong thermodynamic effect.